Bing and Neel Syndrome. (4th September 2012) - Jennane, S.; Doghmi, K.; Mahtat, E. M.; Messaoudi, N.; Varet, B.; Mikdame, M.
Abstract : Introduction . We report the case of a Bing and Neel syndrome revealed by an isolated left ptosis. Case Report . a 57-year-old man was followed up since October 2003 for a typical Waldenström's macroglobulinemia. A first complete remission was obtained with chlorambucil. In August 2004, he relapsed. A second complete remission was obtained with RFC chemotherapy regimen (rituximab, fludarabine, and cyclophosphamide). In October 2009, the patient presented with an isolated left ptosis revealing a Bing and Neel syndrome. The diagnosis was suspected on MRI and confirmed by the detection in the CSF of a monoclonal IgM similar to the one found in the plasma. A quite good partial remission has been obtained after one course of RDHAP (rituximab, dexamethasone, cytarabine, and cisplatin) and 3 courses of RDHOx (rituximab, dexamethasone, cytarabine, and oxaliplatin), in addition to ten intrahectal chemotherapy injections. The treatment was followed by intensification and autologous stem cell transplantation. At D58, the patient died due to a septic shock. Conclusion . BNS is a rare and potentially treatable complication of WM. It should be considered in patients with neurologic symptoms and a history of WM.